From Taboos to Teaching: Strategies for Introducting Puberty in Islamic Religious Education at Primary School - Taja, Nadri; Faqihuddin, Achmad; Hakim , Arif; Muflih, Abdillah (Universitas Islam Indonesia, 2025)
This study examines the role of Islamic Religious Education (PAI) teachers in guiding elementary school students to understand the physical and psychological changes associated with puberty (baligh). Using a qualitative case study approach, data were collected through interviews and classroom observations involving five PAI teachers at Islamic elementary schools in Bandung. The data were analyzed thematically to identify recurring patterns and key categories. The findings reveal six major themes: (1) puberty education as a moral and spiritual responsibility, (2) dialogic and gender-separated instructional strategies, (3) behavioral approaches through counseling and role modeling, (4) integration of religious and general knowledge, (5) collaboration between teachers and parents, and (6) evaluation through observation and self-reflection. These findings indicate that puberty education within Islamic Religious Education should adopt a holistic framework that integrates spiritual, physical, and emotional dimensions. The study highlights the importance of curriculum strengthening, teacher professional development, and parental engagement in supporting effective puberty education grounded in Islamic values.